Optimized control and simulation of a grid-integrated photovoltaic and fuel cell hybrid power system - Satif, Amal; Hlou, Laamari; Elgouri, Rachid (International Journal of Electrical and Computer Engineering (IJECE), 2025)
In this study, we propose an advanced power control strategy tailored for a grid-connected photovoltaic-hydrogen hybrid system aimed at ensuring reliable energy supply to consumers. This hybrid system integrates photovoltaic (PV) panels as the primary energy source supplemented by hydrogen fuel production through electrolysis of surplus PV-generated electricity. To optimize system flexibility and efficiency, we employ several advanced control techniques. A novel maximum power point tracking (MPPT) method, enhanced with a proportional-integral (PI) controller, surpasses conventional perturb and observe (P&O) techniques to maximize PV power output. For precise control of the three-phase photovoltaic inverter, we utilize a space vector pulse width modulation (SVPWM) algorithm. Synchronization with the utility grid is ensured by a phase-locked loop (PLL), maintaining phase coherence between the inverter output and grid supply. The primary goal is to develop a comprehensive and efficient control strategy for grid-connected hybrid systems, addressing both energy generation and storage challenges. MATLAB simulations validate the system's performance, demonstrating high energy conversion efficiency and robust control across varying conditions. This study underscores the potential of hybrid PV-hydrogen systems to provide sustainable and resilient energy solutions for future grid integration.